Uma solução peer-to-peer para a implantação de jogos multiusuário baseada no padrão emergente MPEG-4 MU - Laffranchi, Marcelo Martins (2003)
This work describes the implementation of a support structure to 3D virtual networked games, based on the emergent standard multiuser MPEG-4 in a Gnutella hybrid peer-to-peer network. This solution minimizes the disadvantages of the existent hybrid solutions, that they are based on proxies, which have to be re-configured whenever a new application appears in the net. For that, the code that implements the Gnutella network it was modified from way to include a service of search of games and of active sessions. Two defined components and specified by the emergent standard MPEG-4 MU were implemented and integrated into the Gnutella network for games session control and updating of the scenes. When a node designated as controller leaves, another should assume in a fast and continuous way. Those, among other challenges in the implementation of multiuser games as peer-to-peer applications, they will be discussed in this work, together with the integration of the technologies Gnutella and MPEG-4 MU. The evaluation of this implementation allowed to conclude the some topics about the adaptation of those networks in the support to applications that demand continuous collaboration, as it is the case of a 3D game in that multiples participant constantly alter the scene and also the viability of implementing a session controller in one of the nodes of the network.